Factors That Influence Teachers’ Willingness to Adopt Mobile Technologies: Challenges and Opportunities - Balanyà Rebollo, Judith; De Oliveira, Janaina Minelli (International Journal of Interactive Mobile Technologies (iJIM), 2024)
In today’s digital age, the integration of digital technologies into the educational process has become a priority. The objective of this study is to analyze the conditions under which technology can support teachers in the design, implementation, and evaluation of teachinglearning (E/A) processes. This study specifically sought to answer the research question: “Can a self-evaluation tool help teachers’ guide and design mobile learning activities?” by emphasizing the criterion of effectiveness. Through a qualitative analysis within the framework of the educational design research (EDR) methodology, a series of focus groups were carried out and classified by teachers’ levels of experience, from beginners to experts. These groups provided detailed insights on the perception and use of mobile devices in education, specifically on the use of a self-assessment tool that supports teachers in designing activities with mobile devices. The results indicated a generally positive perception of mobile technologies in education, although variations in adoption and perception were observed depending on the teacher’s level of experience. The mobile self-assessment tool was also commended. The findings support literature on mobile learning and teacher support tools, emphasizing the importance of teaching training and the transformative potential of mobile devices in modern pedagogy.